Competitividad y Emprendimiento: Herramientas de Crecimiento Económico de un país - Gonzaga Añazco, Sandy Jahaira (2017)
This article presents some theories and fundamental assumptions for the development of an entrepreneurial culture as a justification for promoting creative and innovative processes capable of generating productivity and development through the creation of new economic entities at the local, regional and national levels. It seeks to clarify the theoretical construct of entrepreneurship and competitiveness, to identify its fundamental characteristics and to emphasize the importance of them, as economic development tools of the countries.Entrepreneurship has been studied from the perspective of several related sciences, such as economics, psychology, sociology and anthropology. At first, the economy studied entrepreneurship seeking their relationship with development from a purely economic point of view. Subsequently, psychology, sociology and anthropology developed studies of entrepreneurship from a social perspective.To develop this objective, the study and analysis of 16 bibliographical references related to entrepreneurship and competitiveness were considered as fundamental elements of a country's sustainable economic growth. The approach is clearly conceptual and seeks to clarify concepts and encourage future research in relation to entrepreneurship and competitiveness, seeking to determine their importance, especially in emerging economies.